2009
DOI: 10.1002/iroh.200811097
|View full text |Cite
|
Sign up to set email alerts
|

Life History, Reproduction, Growth, Population Dynamics and Production of Gammarus aequicauda (Crustacea: Amphipoda) at Extremely Low Salinities in a Mediterranean Lagoon

Abstract: Aspects of the biology of Gammarus aequicauda were studied at extremely low salinities (0.3-5.7 psu) in Monolimni Lagoon, N. Aegean Sea. Samples were collected monthly from February 1998 to February 1999. Breeding occurred continuously but peaked in late spring, late summer and autumn and three cohorts were produced. The spring and summer cohorts showed fast growth (0.15 mm d -1 ), accelerated maturity and life span of about three and seven months respectively, while the overwintering cohort showed a life span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Furthermore, a higher number of cohorts (12) born during the sampling period could be distinguished at B2 with a life span of 6-7 months, while at D5 only four cohorts occurred with a life span of 7-9 months in cohorts born during winter and early spring and about 12 months in late spring and early summer cohorts. Such a pattern of a longer life span for summer cohorts at D5 is completely different than that observed in other fresh and brackish water gammarids, in which winter cohorts had a longer lifespan (e.g., PÖCKL et al, 2003;SUBIDA et al, 2005;KEVREKIDIS et al, 2009). This can be explained by the negative effect of increasing temperatures on growth and development of spring and early summer cohorts, which thus require a longer time to reach sexual maturity and additionally have a reproductive resting stage that postpones their reproduction and further increases the life span.…”
Section: Population Structure Density and Life History Patternsmentioning
confidence: 84%
“…Furthermore, a higher number of cohorts (12) born during the sampling period could be distinguished at B2 with a life span of 6-7 months, while at D5 only four cohorts occurred with a life span of 7-9 months in cohorts born during winter and early spring and about 12 months in late spring and early summer cohorts. Such a pattern of a longer life span for summer cohorts at D5 is completely different than that observed in other fresh and brackish water gammarids, in which winter cohorts had a longer lifespan (e.g., PÖCKL et al, 2003;SUBIDA et al, 2005;KEVREKIDIS et al, 2009). This can be explained by the negative effect of increasing temperatures on growth and development of spring and early summer cohorts, which thus require a longer time to reach sexual maturity and additionally have a reproductive resting stage that postpones their reproduction and further increases the life span.…”
Section: Population Structure Density and Life History Patternsmentioning
confidence: 84%
“…Kevrekidis et al [14] suggested that the growth and reproductive biology of G. aequicauda are not markedly affected by low salinities. According to the present results, G. aequicauda could well tolerate the salinities that were reported in the study area (4-37 psu) [13].…”
Section: Discussionmentioning
confidence: 99%
“…aequicauda (Martynov, 1931) is one of the most common and abundant amphipods from lagoons and brackish environments of the Mediterranean and the Black Sea [8][9][10][11][12][13][14][15][16][17]. G. aequicauda is a euryhaline species, being very resistant in isolate habitats from the sea with extensive ranges of salinity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations